Empowering Small Electricity Consumers to Help European Member States to Reach the Energy Efficiency Targets of the European Union - González de Uña, Ovidio J.; Carballar Rincón, Alejandro (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2020)
In Europe, small electricity consumers are not using the full potential offered by smart meters. Although the European Union requires Member States to provide consumers with their energy usage data, small consumers are not using this data for improving their energy efficiency. This paper proposes: first, the standardization of the electrical load curve offered to small energy consumers at European level. Second, the use of open innovation challenges as a policy instrument in the European Union to improve the energy efficiency of the small electricity consumers and to encourage the development of new market niches. Finally, the paper quantifies how ICT energy efficiency solutions for small electricity consumers can contribute to the achievement of the 2020 European Union energy efficiency targets.